Memorandum of understanding between Universiti Teknologi MARA and Universiti Malaya / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2020)
On 6th of May 2020, Universiti Teknologi MARA signed a Memorandum of Understanding (MoU) with University Malaya to further strengthen the collaboration between the two higher education institutions.